2019
DOI: 10.1530/eje-18-0411
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS OF ENDOCRINOLOGY: Mechanisms of disease: the endocrinology of obstructive sleep apnoea

Abstract: Obstructive sleep apnoea (OSA) is a common disorder that is associated with serious comorbidities with a negative impact on quality of life, life expectancy and health costs. As OSA is related to obesity and is associated with sleep disruption, increased inflammation and oxidative stress, it is not surprising that OSA has an impact on the secretion of multiple hormones and is implicated in the development of many endocrine conditions. On the other hand, many endocrine conditions that can affect obesity and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 340 publications
(546 reference statements)
0
18
0
3
Order By: Relevance
“…10,11,12,13,14,15 Our group has previously shown a cross-sectional association between OSA and peripheral neuropathy (PN), sight threatening retinopathy, and chronic kidney disease (CKD) in patients with type 2 diabetes. 8,16 We have also shown that OSA was associated with increased risk of renal function decline and development of CKD, and pre-proliferative/proliferative retinopathy in patients with type 2 diabetes in longitudinal studies. 17,18,19 However, these studies were in a relatively small and were from secondary/tertiary care centres.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…10,11,12,13,14,15 Our group has previously shown a cross-sectional association between OSA and peripheral neuropathy (PN), sight threatening retinopathy, and chronic kidney disease (CKD) in patients with type 2 diabetes. 8,16 We have also shown that OSA was associated with increased risk of renal function decline and development of CKD, and pre-proliferative/proliferative retinopathy in patients with type 2 diabetes in longitudinal studies. 17,18,19 However, these studies were in a relatively small and were from secondary/tertiary care centres.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 84%
“…6 Obstructive sleep apnoea (OSA) is common in patients with type 2 diabetes (24-86%) and patients with type 2 diabetes are at increased risk of developing OSA compared to patients without diabetes. 7,8,9 Epidemiological studies in patients without diabetes showed that OSA was associated with increased risk of mortality and CVD (including stroke) which was improved with continuous positive airway pressure (CPAP) in non-randomised studies. 10,11,12,13,14,15 Our group has previously shown a cross-sectional association between OSA and peripheral neuropathy (PN), sight threatening retinopathy, and chronic kidney disease (CKD) in patients with type 2 diabetes.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…OSA is a common complication of obesity [91]. Metformin has been examined through cross sectional and retrospective studies on its impacts on OSA severity.…”
Section: Obstructive Sleep Apnea (Osa)mentioning
confidence: 99%
“…In healthy adults, slow wave sleep suppression has been shown to reduce insulin resistance [41]. In summary, common features observed in OSAS such as nocturnal hypoxemia, arousals from sleep, increased inflammation, and oxidative stress contribute to the development of GMD [42].…”
Section: Discussionmentioning
confidence: 98%